Characterization of LlaKI, a New Metal Ion-Independent Restriction Endonuclease from Lactococcus lactis KLDS4. (30th September 2012) - Belkebir, Abdelkarim; Azeddoug, Houssine
Abstract : Requirement of divalent cations for DNA cleavage is a general feature of type II restriction enzymes with the exception of few members of this group. A new type II restriction endonuclease has been partially purified from Lactococcus lactis KLDS4. The enzyme was denoted as LlaKI and showed to recognize and cleave the same site as FokI. The enzyme displayed a denatured molecular weight of 50 kDa and behaved as a dimer in solution as evidenced by the size exclusion chromatography. To investigate the role of divalent cations in DNA cleavage by LlaKI, digestion reactions were carried out at different Mg 2+, Mn 2+, and Ca 2+ concentrations. Unlike most of type II restriction endonucleases, LlaKI did not require divalent metal ions to cleave DNA and is one of the few metal-independent restriction endonucleases found in bacteria. The enzyme showed near-maximal levels of activity in 10 mM Tris-HCl pH 7.9, 50 mM NaCl, 10 mM MgCl2, and 1 mM dithiothreitol at 30°C. The presence of DNA modification was also determined and was correlated with the correspondent restriction enzyme.